Regional and National Aspects of Intercultural Competence in Teaching DaF - Niyazbekova, Maftuna (The Lingua Spectrum, 2025)
This article addresses some issues of intercultural topics from the perspective of regional and nationally specific characteristics. The problem lies in the fact that, when engaging in discussions of German-language teaching materials, students inadvertently transition into a discussion where the focus shifts to regional and national themes. In this case, the German language becomes not a stumbling block, but a catalyst for an effective communicative act in the process of teaching the German language, which ultimately serves as the final goal of learning any foreign language. The forms of address Siezen” (formal “You”) and “Duzen” (informal “You”) are chosen as the subject of discussion, as they differ in function not only from an international, but also from a regional and national perspective. This approach makes it possible to consider German language teaching not merely as the mechanical acquisition of grammar and vocabulary, but as the development of intercultural competence that integrates social norms, cultural traditions, and mentalities. The analysis demonstrates that teaching DaF in an intercultural dimension enhances students’ ability to adapt flexibly to diverse communicative contexts.